PENGARUH KONFLIK KERJA DAN BEBAN KERJA TERHADAP STRES KERJA YANG BERDAMPAK PADA PRODUKTIVITAS KERJA KARYAWAN [STUDI KASUS DI PT. LA LUNA SEMARANG) - Patricia Dhiana Paramita (Jurnal Ekonomi dan Bisnis Kontemporer, 2019)
PT. La Luna Semarang is a company engaged in the manufacture of women'sclothing from brocade experiencing problems, where employee work productivity,especially the production part is still low, where it is allegedly motivated by frequentconflicts between fellow co-workers as well as between employees with superiors andworkloads that are overload, which is not according to the ability of employees. Thepurpose of this study is to determine the effect of work conflicts and employee workloadpartially and simultaneously on work stress and employee work productivity and to findout whether work stress mediates the effect of work conflict and workload on workproductivity.The population in this study all employees of the production section of PT. LaLuna Semarang, amounting to 70 people. The number of samples taken in this researchwas determined through the census method, by taking a sample of 70 people or overallof the total population of employees who work in the production of PT. La LunaSemarang. The data analysis technique used is Two Stage Least Square (2SLS), modelsuitability test and path analysis.The calculation results show that work conflict and workload partially havea positive and significant effect on work stress and work productivity, work stresshas a positive and significant effect on work productivity, work stress doesn’t mediatethe effect of work conflict on work productivity and work stress doesn’t mediate theeffect of workload on work productivity.The management of PT. La Luna eliminates the occurrence of work stress amongemployees by making policies not haphazard so as not to cause work conflicts betweencolleagues and between employees and superiors and to provide workloads inaccordance with employee capabilities, which will have a positive impact on employeeproductivity.Keywords: work conflict, work load, work stress and work productivity